KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI: PENGARUHNYA TERHADAP KINERJA YANG DIMEDIASI DENGAN KOMITMEN ORGANISASI - M.Derry Emil Salim; Anis Fuad (Jurnal Manajemen Retail, 2021)
One of the ways to improve employee performance can be achieved by applying astrong leadership style and organizational culture. This study aims to examine the effectof transformational leadership style and organizational culture in improving employeeperformance through organizational commitment as intervening. The study wasconducted on 100 employees (land / ship) at PT Aman Lintas Samudra. Data analysisused the SEM-PLS method with the SmartPLS version 2.3.m3 application. Thehypothesis test results prove that transformational leadership style and organizationalculture have a significant positive effect on organizational commitment and employeeperformance. Organizational culture has the most dominant influence both onorganizational commitment and employee performance. The mediation test resultsprove that organizational commitment does not mediate the influence oftransformational leadership style and organizational culture on employee performance